2016
DOI: 10.3171/2015.1.jns141766
|View full text |Cite
|
Sign up to set email alerts
|

Height of aneurysm neck and estimated extent of brain retraction: powerful predictors of olfactory dysfunction after surgery for unruptured anterior communicating artery aneurysms

Abstract: A pterionAl approach and its modifications are commonly used for clipping most anterior circulation aneurysms. In such an approach, the frontal lobe and olfactory nerve are both retracted to some degree to access aneurysms located in the circle of Willis. In particular, in cases of an anterior communicating artery (ACoA) aneurysm, a retractor is placed across the olfactory tract, which is damaged primarily by retractor pressure and strain. Thus, olfactory dysfunction following a pterional approach occurs most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Park et al reported objective olfactory dysfunction rate of 10.8% in their study. 16 Because of the risks of these complications, minimal invasive surgery like keyhole approach with eyebrow or palpebral incision was introduced in AcomA surgery. [17][18][19] These approaches reduced the amount of brain retraction and rectus gyrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al reported objective olfactory dysfunction rate of 10.8% in their study. 16 Because of the risks of these complications, minimal invasive surgery like keyhole approach with eyebrow or palpebral incision was introduced in AcomA surgery. [17][18][19] These approaches reduced the amount of brain retraction and rectus gyrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying olfactory decline are multifactorial and not entirely understood (Murphy, ; Doty and Kamath, ; Mobley et al, ; Patel and Pinto, ; Attems et al, ). Park et al () analyzed 102 patients with unruptured ACOM aneurysms who underwent a pterional or supraorbital keyhole craniotomy for aneurysm clipping. They found aneurysm neck height >9 mm and estimated brain retraction >12 mm to be predictors for postoperative olfactory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…They did not find differences in bilateral anosmia rates based on age, history of aSAH, sex, or surgical approach. Major limitations, however, are lack of individual testing of each nostril, lack of preoperative assessment and postoperative assessment only in those patients that reported subjective olfactory impairment (Park et al, ). In 2009, Moman et al () interviewed 32 patients who underwent clipping of an unruptured aneurysm since 1991.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T O THE EDITOR: We have read with great attention the article by Park et al 8 (Park J, Son W, Kwak Y, et al: Pterional versus superciliary keyhole approach: direct comparison of approach-related complaints and satisfaction in the same patient. J Neurosurg [epub ahead of print March 2, 2018.…”
mentioning
confidence: 99%